The Effect of Environmental Awareness, Waste Management, and Palm Oil Processing Technology on the Reputation of Palm Oil Companies in Kalimantan - Judijanto, Loso; Arini, Rani Eka; Novitasari, Salwa Aulia (Westscience Press, 2024)
This study examines the impact of Environmental Awareness, Waste Management practices, and Palm Oil Processing Technology on the Corporate Reputation of palm oil companies in Kalimantan. Using a quantitative approach, data was gathered from 210 respondents affiliated with various companies in the sector. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to analyze the data, with findings indicating that all three variables significantly influence Corporate Reputation. Environmental Awareness and Waste Management were found to positively impact reputation, with Processing Technology demonstrating the strongest effect, underscoring the critical role of technological innovation in reputation management. The study suggests that palm oil companies can enhance their public perception and credibility by adopting sustainable practices and investing in advanced processing technology. These findings offer actionable insights for industry stakeholders seeking to align their operations with environmental and technological advancements.